A Translation Analysis Of Unit Shift In A Study In Scarlet Sherlock Holmes Novel And Its Translation - Hidayati, Noviyana, Dr. Dwi Haryanti, M.Hum, Mauly Halwat Hikmat, Ph. D (2016)
This research focused on the translation analysis of unit shift in A Study in Scarlet Sherlock Holmes. The objective of this research are (1) to classify the types of unit shifts found in novel A Study in Scarlet Sherlock Holmes and (2) to describe the equivalent of unit shift in the novel A Study in Scarlet Sherlock Holmes and its translation. The limitation of this research is on word, phrase, clause, sentences and their translation consisting of Unit shift. This research describes about unit shifts based on Catford's theory shifts in translation. The method of this research is qualitative-descriptive method. The data are sentences containing unit shift and the data source is a novel entitled A Study in Scarlet Sherlock Holmes and its translation. The writer uses the documentation technique to collect the data. Afterward, to evidence the validity of data, the writer uses the triangulation where the data sources are from the novel and informant. The result of this research shows that there are 8 types of unit shift which occurs from (1) word translated into phrase occurs in 230 data or 67,45%, (2) phrase translated into word occurs in 79 data or 23,17% , (3) phrase translated into sentence occurs in 2 data or 0,59%, (4) clause translated into word occurs in 2 data or 0,59%, (5) clause translated into phrase occurs in 6 data or 1,76%, (6) sentence translated into word occurs in 2 data or 0,59%, (7) sentence translated into phrase occurs in 18 data or 5,28%, (8) sentence translated into clause occurs in 2 data or 0,59%. The equivalent of unit shift translation is divided into two, namely; equivalent translation and non equivalent translation. The equivalent translation occurs in 341 data or 100% of data and none of them included non equivalent translation. Keywords: translation, unit shift, equivalence